Variaciones de la luz - Bellessi, Diana, 1946- (Madrid : Visor Libros, 2011)
Poems.
XXXII Premio Internacional de Poesía Ciudad de Melilla
Online resource; title from PDF title page (Digitalia, viewed September 2, 2017)
Keywords: Electronic books; Poetry